2008
DOI: 10.1186/1475-2875-7-131
|View full text |Cite
|
Sign up to set email alerts
|

Competency of Anopheles stephensi mysorensis strain for Plasmodium vivax and the role of inhibitory carbohydrates to block its sporogonic cycle

Abstract: Background: Despite the abundance of studies conducted on the role of mosquitoes in malaria transmission, the biology and interaction of Plasmodium with its insect host still holds many mysteries. This paper provides the first study to follow the sporogonic cycle of Plasmodium vivax in a wild insecticide-resistant mysorensis strain of Anopheles stephensi, a major vector of vivax malaria in south-eastern Iran. The study subsequently demonstrates that host-parasite sugar binding interactions are critical to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…stephensi was the most dominant species. This species has been recognized as a chief malaria vector in southern Iran [10, 15] and recently it has been shown that this species has high fitness to transmit Plasmodium vivax in Baluchestan area [26]. Previous studies in India also showed that this species plays a major role in malaria transmission in continental India because of its predominantly domestic habits and its behavior [27].…”
Section: Discussionmentioning
confidence: 99%
“…stephensi was the most dominant species. This species has been recognized as a chief malaria vector in southern Iran [10, 15] and recently it has been shown that this species has high fitness to transmit Plasmodium vivax in Baluchestan area [26]. Previous studies in India also showed that this species plays a major role in malaria transmission in continental India because of its predominantly domestic habits and its behavior [27].…”
Section: Discussionmentioning
confidence: 99%
“…An. stephensi has been experimentally infected with P. vivax from infected monkeys (Basseri et al, 2008;Collins et al, 2009) and humans (Adak et al, 2005); both oocysts and sporozoites found were found in the mosquitoes.…”
Section: Continuedmentioning
confidence: 99%
“…Suleman et al [37] demonstrated intra-specific variation in the reproductive capacity of A. stephensi but there was no evidence that this species constituted a species complex. The mysorensis form of this species has been recognized as the main vector of malaria in southeastern Iran [38]–[39], while in India it is considered to be a rural species with poor vectorial capacity for both vivax and falciparum malaria. In contrast, the type form is recognized as an efficient vector of urban malaria in India [32].…”
Section: Introductionmentioning
confidence: 99%